An engineered abcb4 expression model reveals the central role of NF‐κB in the regulation of drug resistance in zebrafish. Issue 4 (14th February 2022) - Sun, Cong‐Jie; Hu, Rong‐Yin; Li, Zhi‐Cao; Jin, Lu; Lu, He; He, Zhi‐Xu; Shu, Li‐Ping
Abstract: Multi‐drug resistance (MDR) is a phenomenon that tumor cells are exposed to a chemotherapeutic drug for a long time and then develop resistance to a variety of other anticancer drugs with different structures and different mechanisms. The in vitro studies of tumor cell lines cannot systematically reflect the role of MDR gene in vivo, and the cost of in vivo studies of transgenic mice as animal models is high. Given the myriad merits of zebrafish relative to other animal models, we aimed to establish a screening system using zebrafish stably expressing ATP‐binding cassette (ATP‐cassette) superfamily transporters and unveil the potential regulatory mechanism. We first used the Tol2‐mediated approach to construct a Tg ( abcb4:EGFP ) transgenic zebrafish line with ATP‐binding cassette (ABC) subfamily B member 4 (abcb4) gene promoter to drive EGFP expression. The expression levels of abcb4 and EGFP were significantly increased when Tg(abcb4:EGFP) transgenic zebrafish embryos were exposed to doxorubicin (DOX) or vincristine (VCR), and the increases were accompanied by a marked decreased accumulation of rhodamine B (RhB) in embryos, indicating a remarkable increase in DOX or VCR efflux. Mechanistically, Akt and Erk signalings were activated upon the treatment with DOX or VCR. With the application of Akt and Erk inhibitors, drug resistance was reversed with differing responsive effects. Notably, downstream NF‐κB played a central role in the regulation of abcb4‐mediated drug resistance. Taken together, the data indicate that the engineered Tg(abcb4:EGFP) transgenic zebrafish model is a new platform for screening drug resistance in vivo, which may facilitate and accelerate the process of drug development.